Patient-Reported Symptoms and Sequelae 12 Months After COVID-19 in Hospitalized Adults: A Multicenter Long-Term Follow-Up Study - Comelli, Agnese; Viero, Giulia; Bettini, Greta; Nobili, Alessandro; Tettamanti, Mauro; Galbussera, Alessia Antonella; Muscatello, Antonio; Mantero, Marco; Canetta, Ciro; Martinelli Boneschi, Filippo; Arighi, Andrea; Brambilla, Paolo; et al. (Frontiers in Medicine, 2022)
OBJECTIVE: although clinically relevant, our knowledge on long-term consequences of COVID-19 is still scarce. The aim of this study was to analyse patient-reported outcomes, including assessment by specific questionnaires of health impairment and symptoms. METHODS: This is a prospective, observational and multicentre study promoted by Fondazione IRCSS Ca’ Granda Ospedale Maggiore Policlinico di Milano and Istituto di Ricerche Farmacologiche Mario Negri IRCCS including 8 hospitals located in North and Central Italy. A telephone interview to assess rehospitalization, access to health care resources, health impairment and symptoms was performed at 12 months after the discharge in patients admitted to hospital because of COVID19 from the beginning of the pandemic to the end of May 20. RESULTS: Among the 776 patients discharged alive, 44 (5.7%) died, 456 subjects (58.8%) completed the questionnaire and 276 (35.6%) were not reachable or refused to join the telephone interview. The mean age of the study population was 59.4 years (SD 14.1), 69.8% of individuals needed oxygen support during hospitalization and 10.4% were admitted to ICU. Overall, 91.7% of participants reported at least one symptom/sequela at 12 months. Exertional dyspnoea (71.7%), fatigue (54.6%) and gastrointestinal symptoms (32.8%) were the most reported ones. Health issues after discharge including hospitalization or access to emergency room were described by 19.4% of subjects. Female and presence of comorbidities were the principal predictors of deterioration in health status and presence of >=2 symptoms/sequelae. CONCLUSIONS: Patient-reported symptoms and sequelae, principally dyspnoea and fatigue, are found in most individuals even 12 months from COVID-19 hospitalization. Long-term follow-up based on patient-centred outcome can contribute to plan tailored interventions.